Secondary Level English Language Teachers’ Professional Development: Perceptions and Practices - Saud, Mahesh Singh (Exploration अन्वेषण, 2026)
Professional development is mandatory for addressing contextual realities and enhancing the professional knowledge, attitudes and skills of teachers. However, in the context of developing countries like Nepal, only limited forms or ways of professional development have been in practice. Considering the reality, this study explored the English language teachers’ perceptions and practices in the case of their professional development. For this study, I used a narrative inquiry method. Moreover, I interviewed four secondary-level English teachers from Darchula and Baitadi (two hilly) districts of Sudurpashchim province. The findings of this study were discussed under four themes such as English language teachers’ perception of professional development, the importance of English language teachers’ professional development, English language teachers’ practices for their professional development and English language teachers’ challenges in their professional development. The study found that the participant teachers perceive professional development as a process and practice. It was also found that teachers watch ELT videos, read online and printed materials, write on ELT issues and attend training, conferences and workshops for their professional development. Moreover, the internet issue, less issue-focused professional events and a lack of school and concerned authority support were the challenges to their professional development.